Back to the Future - The Scientific Exploration of An Ancient Medicinal Plant - Gericke, Nigel (My University, 2016)
Alkaloids are active compounds found in plants. In the conference has been reviewed new sceletium alkaloids isolated from african plants.
Keywords: Alcaloides; Natural Products; Alkaloids; Activity